Indigenous cattle genetic resources, their husbandry practices and breeding objectives in North-western Ethiopia - Wuletaw, Z. (2004)
Phenotypic as well as genetic characterization of indigenous livestock genetic resources provides the basis for any livestock development intervention. However, in Ethiopia, little attention has been given to identify, characterize and conserve the diversity of the various livestock breed types. It is with this understanding that the present study was initiated and conducted in North and South Gondar zones with the view to characterize indigenous cattle breeds/population, identify.’ the main problems, and outline intervention for genetic improvement of the identified breed populations based on farmer trait preferences. Six sample sites were selected based on initial rapid survey conducted at the start of the study. Three defferent survey techniques; namely focus group discussion, administration of semi—structures questionnaires on husbandiy practices and indicative production and reproduction performance, and phenotypic distance measurements were employed. Findings of the focus group revealed that each of the cattle breed types of the respective study sites were markedly dfferent in phenotypic characteristics. Findings from the semi-structured interviews revealed that the indigenous cattle breed types are multipurpose production and input functions, adapted to wide range of environments, and managed under traditional and largely subsistent mode of production. Furthermore, farmers were interested to improve their local genotypes and suggested different target traits for improvement. Based on these farmers traits preferences village breeding scheme is proposed through the provision of genetically selected breeding bulls. Overall lactation length, and average daily milk yield of this study are higher than national average figures of 1.17 litre per day and 6.33 months, respectively. Reported figures for age at first calving from the different study sites have been found longer than the overall estimated value for Bos indicus. The over all mean value of 14.5 years for longevity exceeds the figure for most African cattle of 10 to 13 years. The reported critical constraints of traditional cattle production were seasonal feed shortage, high disease challenges, weak infrastructure, lack or shortage of working capital, weak cattle markets and cattle raiding. For a phenotypic distance study a total of 1623 sample animals were recorded and ident ified by sex, dentition, and some discrete variables. Linear measurements on 12 traits were taken from 708 female and 146 male mature animals. Categorical body forms and types were recorded from these as well as the rest of the sample animals too. The general linear model was used to analyse variance on the 12 quantitative traits between sites for males and females separately. Tukey’s multiple comparison test showed that each of the 12 quantitative traits were highly significant (p<. 0001). The model filled for the male populations explained variation ranging from 35.2 to 67.2%, whereas the model explained 34.7 to 56.1% of the variation in the female population. For the categorical variables chi -square test was employed, and found, for most of the variables, highly significant (p<.0001,). Following this other statistics derived from the Pearson chi-square were used to measure the level of association. Furthermore, multiple mean comparisons were also made for these categorical variables using Bonferroni ‘s correction. Mulltivariate analyses were applied separately to females and males. The resultant discriminant function resulted in a hit ratio of 73.8 and 80.5% for female and male populations, respectively. Canonical discrimninant analysis for females and males showed highly significant (p<.0001) Mahalanobis distances between sites. The multivariate test for differences between the sites is also highly significant (p<.0001 ) in all of the four types of multivariate tests. The step-wise discriminant analysis for both male and female sample populations showed that all variables had highly significant (P<. 0001) contribution for explaining the variation in the model. Trees/phenogram constructed separately for male and female populations revealed the existence of four distinct clusters in both sexess. The tree topologies as well as the branch length somehow differ between the sexes. The reliability of the phenogram/dendrogram was tested by the bootstrap method and the result showed that both trees were supported by the high to moderate bootstrap values. In general both the categorical and quantitative variables have dfferentiated the sample populations in, to four to six different classes. Thus, indigenous cattle populations under traditional management in North Gondar as well as parts of South Gondar zones are heterogomzous populations divisible into distinct breed types based on phenotypic distance of some quantitative traits and analysis of qualitative variables.